Response to intranasal Lactococcus lactis W136 probiotic supplementation in refractory CRS is associated with modulation of non-type 2 inflammation and epithelial regeneration - Al-Romaih, Saud; Harati, Oumkaltoum; Mfuna, Leandra Endam; Filali-Mouhim, Ali; Pelletier, Audrey; Renteria Flores, Axel; Desrosiers, Martin (Frontiers in Allergy, 2023)
JUSTIFICATION: We have previously documented (1) that in individuals with chronic rhinosinusitis (CRS) refractory to surgery, intranasal application of live Lactococcus lactis W136, a probiotic bacterium, improves sinus-specific symptoms, SNOT-22, and mucosal aspect on endoscopy, accompanied by a reduction in sinus pathogens and an increase in protective bacteria. The present work explores the molecular mechanisms underpinning these observations using transcriptomics of the sinus mucosa. METHOD: Epithelial brushings collected prospectively as a sub-study of the L. lactis W136 clinical trial were used to probe epithelial responses to microbiome supplementation using a hypothesis-free bioinformatic analysis of gene expression analysis. Samples from twenty-four patients with CRS refractory to medical and surgical management were prospectively collected during a clinical trial assessing the effect of 14 days of BID nasal irrigation with 1.2 billion CFU of live L. lactis W136 probiotic bacteria (CRSwNP=17, CRSsNP=7). Endoscopically guided sinus brushings were collected as part of the initial study, with brushings performed immediately before and after treatment. Following RNA extraction, samples were assessed using the Illumina HumanHT-12 V4 BeadChip. Differential gene expression was calculated, and pathway enrichment analysis was performed to identify potentially implicated processes. RESULTS: Differentially identified transcripts and pathways were assessed for the overall population and the clinical phenotypes of CRSwNP and CRSsNP. Patterns of response to treatment were similar across all groups, implicating pathways for the regulation of immunity and epithelial cell regulation. These resemble the patterns of improvement observed following successful treatment with endoscopic sinus surgery or azithromycin. CONCLUSION: Gene expression profiling following the application of live bacteria to the diseased sinus epithelium highlights the implication of multiple components of the inflammation-microbiome-epithelial barrier axis implicated in CRS. These effects appear to involve both epithelial restoration and modulation of innate and adaptive immunity, supporting the potential interest of targeting the sinus epithelium and the microbiome as potential CRS therapies.